Percepción del profesionalismo médico por internos de medicina - Linares Hurtado, Luis Harvey Manuel (2019)
Objetive: To identify the perception of the professionalism by medical interns. Materials and methods: This is a transversal-descriptive study. We used a validated questionnaire used in the research of Asghari and col, and traduced by Gutiérrez. We identified the professional aspects perceived, in faculties and medical residents, by 56 medical interns during their internship in Belen Hospital of Trujillo during 2018. Results: The mean score on observing professionalism was 50.8/70 and 50.6/70 for faculty and residents respectively. The most observed professional aspect in faculties was respect followed in descending order by responsibility, altruism, honor and integrity, justice and excellence. In medical residents, it was responsibility, respect, justice, altruism, excellence, and honor and integrity. Conclusions: Accord with medical interns’ perception, the faculties achieved 72.6% of maximum score of the medical professionalism and the residents 72.3%.